The Influence of Human Resource Practices, Inclusive Leadership, and Digital Competence on Employee Engagement and Retention in the Hospitality Industry: A SEM-PLS Approach - Yadnya, I Dewa Gede Sayang Adi; Khamiliyah, Lili (Integrasi Sains Media, 2024)
This study investigates the direct effects of human resource practices, inclusive leadership, and digital competence on employee engagement, job satisfaction, and retention intention in the hospitality industry. Grounded in Social Exchange Theory (SET) and the Job Demands–Resources (JD-R) Model, the research aims to provide a multidimensional understanding of how organizational support and digital adaptability shape key employee outcomes in service-intensive contexts. A quantitative, cross-sectional survey was conducted with 312 hospitality employees across Indonesia. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 4. The measurement model was assessed for validity and reliability, followed by an evaluation of the structural model to test the proposed hypotheses. The results confirm that human resource practices, inclusive leadership, and digital competence each have significant positive effects on employee engagement, job satisfaction, and retention intention. Moreover, both engagement and satisfaction were found to be strong predictors of employees’ intent to stay. These findings highlight the importance of integrating psychosocial and digital resources within human capital strategies. This study extends the existing literature by incorporating digital competence and inclusive leadership as key antecedents of employee outcomes—areas that remain underexplored in hospitality research. It also addresses a geographical gap by focusing on an emerging market context. The study offers theoretical integration of SET and JD-R models and provides actionable insights for organizations seeking to enhance workforce sustainability in a post-pandemic, digitally evolving service landscape.